2015
DOI: 10.1002/anie.201508036
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Isopropylzinc Alkoxide of Pyrimidyl Alkanol: Mechanistic Insights for Asymmetric Autocatalysis with Amplification of Enantiomeric Excess

Abstract: Asymmetric amplification during self-replication is a key feature that is used to explain the origin of homochirality. Asymmetric autocatalysis of pyrimidyl alkanol in the asymmetric addition of diisopropylzinc to pyrimidine-5-carbaldehyde is a unique example of this phenomenon. Crystallization of zinc alkoxides of this 5-pyrimidyl alkanol and single-crystal X-ray diffraction analysis of the alkoxide crystals reveal the existence of tetramer or higher oligomer structures in this asymmetric autocatalytic system. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 111 publications
0
44
0
Order By: Relevance
“…Initial mechanistic models proposed the catalytically active species to be dimeric, but NMR and microcalorimetry experiments conducted since strongly suggest the catalytically competent assemblies to be at least tetrameric in ligand . Crystallographic studies showed racemic tetramers to be structurally distinct from the enantiopure ones (Figure ), which is likely connected with the reactivity and the unique stereochemical outcomes of this autocatalytic reaction …”
Section: Figurementioning
confidence: 98%
“…Initial mechanistic models proposed the catalytically active species to be dimeric, but NMR and microcalorimetry experiments conducted since strongly suggest the catalytically competent assemblies to be at least tetrameric in ligand . Crystallographic studies showed racemic tetramers to be structurally distinct from the enantiopure ones (Figure ), which is likely connected with the reactivity and the unique stereochemical outcomes of this autocatalytic reaction …”
Section: Figurementioning
confidence: 98%
“…In this substructure, four Zn atoms and four O atoms form a virtual cube-like polyhedron, as shown in Figure 3B. Interestingly this hypothetical structural element also appears in the X-ray structure of the "enantiomeric" model compound of the Soai autocatalysis, reported very recently by Matsumoto et al [47]. It should be mentioned that the symmetries of compound S-E4 are valid only if the isotopic composition of the central O2Zn2 ring is disregarded.…”
Section: Zinc Isotopic Chirality?mentioning
confidence: 52%
“…Some fragments of hypothetic intermediates [44][45][46] of the Soai autocatalysis show chiral arrangement of the Zn atoms. One of these fragments, the structure of which has been essentially supported by X-ray crystallography [47], will also be included in the present study. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations